Validity Aspects of the Strengths and Difficulties Questionnaire (SDQ) Adolescent Self-Report and Parent-Report Versions Among Dutch Adolescents. (March 2021) - Vugteveen, Jorien; de Bildt, Annelies; Theunissen, Meinou; Reijneveld, Sijmen A.; Timmerman, Marieke
In this study, validity aspects of the Strengths and Difficulties Questionnaire (SDQ) self-report and parent-report versions were assessed among Dutch adolescents aged 12 to 17 years (community sample: n = 962, clinical sample: n = 4, 053). The findings mostly support the continued use of both SDQ versions in screening for psychosocial problems as (a) exploratory structural equation analyses partially supported the grouping of items into five scales; (b) investigation of associations between scales of the SDQ and the Child Behavior Checklist, Youth Self-Report, and Intelligence Development Scales-2 provided evidence for the SDQ versions' convergent and divergent validity; and (c) receiver operating characteristics curves yielded evidence for both SDQ versions' criterion validity by showing that these questionnaires can be used to screen for psychosocial problems, except for the adolescent-reported version for males. Regardless of the adolescent's gender, the receiver operating characteristics curves showed both SDQ versions to be useful for screening for three specific types of problems: anxiety/mood disorder, conduct/oppositional deviant disorder, and attention-deficit/hyperactivity disorder. Additionally, parent-rated SDQ scores were found to be useful for screening for autism spectrum disorder.